2020
DOI: 10.1002/pd.5869
|View full text |Cite
|
Sign up to set email alerts
|

Fetal dural sinus thrombosis: A systematic review

Abstract: Introduction Fetal dural sinus thrombosis (DST) is a rare condition. Although numerous case reports exist, the findings appear heterogenous and providing accurate patient counselling remains challenging. Methods A systematic literature review was conducted in accordance with PRISMA guidance. Results Thirty‐one studies including 78 patients were included in this review. No association with maternal or neonatal coagulopathy, infection or trauma was found. The average gestational age at diagnosis was 25 weeks (ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The quantitative data on the cross-sectional area of the fetal straight sinus in the present study may be useful for making a differential diagnosis between these two aspects. Fetal hypoplasia or atresia of the straight sinus may result in degenerative failure and the formation of a permanent falciform vein (17).…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative data on the cross-sectional area of the fetal straight sinus in the present study may be useful for making a differential diagnosis between these two aspects. Fetal hypoplasia or atresia of the straight sinus may result in degenerative failure and the formation of a permanent falciform vein (17).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Sacco et al 2 published in November 2020 identified just 78 cases, with the earliest case described in 2000. As with our case, the review observed no association between fetal dural sinus thrombosis and any identifiable maternal or neonatal coagulopathy, infection or trauma.…”
Section: Discussionmentioning
confidence: 99%